Analyzing the Effectivity of Android-Based Application to Increase Physical Performance and Reduce Injuries Potentials During Fitness Training - Istighfarin, Rahmatul Istighfarin; Dewi, Ratna Sari Dewi; Sudiarno, Adithya Sudiarno; Sinaga, Romando Sinaga (JURNAL TEKNIK INDUSTRI, 2024)
Fitness centers are the favorite place for most urban communities to do physical fitness training activities. However, among the millions who practice fitness in the gym, only certain people know how to exercise using gym equipment correctly. One alternative solution to overcome the problem is using a personal trainer application based on android. Android-based applications are used in this research because it is easier to use than the physical fitness guidebook and cheaper than hiring a personal trainer. This research recruits ten people to prove increased physical performance after using an android-based application by doing fitness training with and without an android-based application. The test will measure at two conditions. The first condition is that right after fitness training, the respondent will measure physical performance analysis using Nordic Body Map (NBM) Questionnaire and maximum oxygen volume. Second, twenty-four hours after fitness training, the respondent’s physical performance was measured again using NBM and Mc Gill Pain questionnaire to measure Delayed Onset Muscle Soreness (DOMS). After fitness training activities with the android-based application, there is an increase in physical performance and reduced injury potential, which can be seen from a significantly reduced DOMS score from Mc Gill Pain questionnaire. However, NBM score and maximum oxygen volume result are insignificant.